2014
DOI: 10.14804/1-1-25
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Clinical Preceptors

Abstract: Nursing students in South Africa are mostly dissatisfied with clinical teaching and accompaniment in clinical practice. Consequently final year students feel ill prepared for their roles as registered nurses. Many factors, for example the shift from hospital based training to higher education, staff shortages, high acuity levels, greater treatment sophistication etc contribute to the dilemma of inadequate support of students during clinical placements. Preceptors that are either appointed by the nursing educat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 27 publications
(40 reference statements)
0
16
0
Order By: Relevance
“…It is, therefore, recommended that institutions that engage preceptors in training and assessing students in distributed health professionals’ education should ensure initial training and ongoing support for the preceptors. A programme similar to the nurse preceptor training programmes reported by Botma et al 21 that are carried out at two South African universities would be useful in improving workplace-based learning and assessment. We further recommend that institutions pay attention to factors that affect the reliability of preceptor assessment in distributed medical education so as to optimise the benefits of workplace assessment environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is, therefore, recommended that institutions that engage preceptors in training and assessing students in distributed health professionals’ education should ensure initial training and ongoing support for the preceptors. A programme similar to the nurse preceptor training programmes reported by Botma et al 21 that are carried out at two South African universities would be useful in improving workplace-based learning and assessment. We further recommend that institutions pay attention to factors that affect the reliability of preceptor assessment in distributed medical education so as to optimise the benefits of workplace assessment environment.…”
Section: Discussionmentioning
confidence: 99%
“…This not only enhances the quality of assessment, but also contributes to faculty development in primary healthcare settings and improves patient management. Botma et al 21 provide insight into a programme that has been used by two universities to train nurse preceptors in South Africa.…”
Section: Introductionmentioning
confidence: 99%
“…Preceptors are professionals with adequate knowledge and skills to support students during clinical placement. Preceptors are often employed by academic institutions in part-time or fulltime positions to serve as teachers in the clinical setting (Botma et al, 2012). In Ghana, preceptors are often full-time employees of the clinical facilities which may affect their availability to interact with and support students due to conflicting responsibilities.…”
Section: Introductionmentioning
confidence: 99%
“…This continuous development programme was an 80-h, eight-credit short course that included a clinical component (Jeggels et al 2013 :3). While, Botma, Jeggels and Uys ( 2012 :6) found that a preceptorship programme is now also offered at the University of the Free State (UFS) and with a copious amount of homework. The preceptorship programme is based on the preceptorship module that involves all stakeholders, for example, preceptor, student, university and clinical institution (Botma et al 2012 :9).…”
Section: Introductionmentioning
confidence: 99%
“…While, Botma, Jeggels and Uys ( 2012 :6) found that a preceptorship programme is now also offered at the University of the Free State (UFS) and with a copious amount of homework. The preceptorship programme is based on the preceptorship module that involves all stakeholders, for example, preceptor, student, university and clinical institution (Botma et al 2012 :9). The authors further added that the UFS, so far, has only trained their staff and was planning to roll out the preceptor training programme further.…”
Section: Introductionmentioning
confidence: 99%